Atrial fibrillation and heart failure: Factors influencing the choice of oral anticoagulant. (15th January 2017) - Brown, Louise A E; Boos, Christopher J
Abstract: Atrial fibrillation (AF) and heart failure (HF) frequently coexist. AF is identified in approximately one third of patients with HF and is linked to increased morbidity and mortality than from either condition alone. AF is relatively more common in HF with preserved ejection fraction (HFpEF) than with reduced ejection fraction (HFrEF). Nevertheless, the risk of stroke and systemic embolism (SSE) is significantly increased with both HF types and the absolute risk is heavily influenced by the presence and severity of associated additional stroke risk factors. The European Society of Cardiology has very recently introduced a third HF subtype entitled HF with mid-range ejection fraction (HFmrEF). At present oral anticoagulation is recommended for all patients with AF and HF, independent of HF type. In addition to warfarin there are currently four non-vitamin K oral anticoagulants (NOACs, previously called novel oral anticoagulants) that have been approved for the prevention of SSE. They consist of one direct thrombin inhibitor, dabigatran and three factor Xa inhibitors: rivaroxaban, apixaban and, most recently, edoxaban. In this review article we present an overview of the evidence to support the use of NOACs for the prevention of SSE in patients with AF and HF and review the influence of HF subtype and co-morbidities on the potential choice of oral anticoagulant. Highlights: Heart failure and atrial fibrillation frequently coexist, and combined, lead to increased morbidity and mortality. NOACs are favoured in the majority of patients due to ease of use, more favourable bleeding profile and fewer interactions. Heart failure subtype may influence other risk factors, but is not a determinant for choice of anticoagulation.